HCl Treatment of Mixed-Phase MoVTeNbOx Catalysts for Enhanced Performance in Selective Oxidation of Propane - Wei, Zeyue; Zhang, Hanzhi; Bai, Yunxing; Zhang, Xuanyu; Huang, Weixin (Precision Chemistry, 2025)
Hydrothermally synthesized mixed-phase MoVTeNbO x catalysts are active for catalyzing the selective oxidation of propane to acrylic acid but suffer from the presence of the amorphous phase and low specific surface areas. Herein we report that HCl treatment preferentially dissolves the amorphous phase in hydrothermally synthesized mixed-phase MoVTeNbO x catalysts and increases the catalytic performance. An optimal HCl treatment significantly increases the C 3 H 8 conversion from 38.9% to 58.2% without changing the acrylic acid selectivity in the selective oxidation of propane to acrylic acid at 380 °C. The original and HCl treated catalysts exhibit similar apparent activation energies, while HCl treatment increases the specific surface area, surface acid sites, surface V 5+ density, and C 3 H 8 and C 3 H 6 irreversible adsorption amounts but decreases the C 3 H 8 and C 3 H 6 irreversible adsorption heats. The C 3 H 8 conversion rate is proportional to the surface V 5+ density and C 3 H 8 irreversible adsorption amount, and the TOF is measured as 3.31 ± 0.08 × 10 –5 s –1 at 340 °C. Thus, HCl treatment enhances the catalytic performance of mixed-phase MoVTeNbO x catalysts mainly by increasing the active site density rather than by increasing the active site activity. Our results provide an effective approach to prepare highly active mixed-phase MoVTeNbO x catalysts for the selective oxidation of propane to acrylic acid.